SHPB test analysis and a constitutive model for frozen soil under multiaxial loading. (April 2020) - Zhu, Zhiwu; Cao, Chenxu; Fu, Tiantian
A split Hopkinson pressure bar is adopted to test the dynamic mechanical behavior of frozen soil at different temperatures and high strain rates. An aluminum sleeve is used as a passive confining pressure device. Comparing the results of this test with those under the uniaxial state shows that besides the temperature and strain rate effects, frozen soil exhibits obvious stress strengthening characteristics. In addition, the failure mode is viscoplastic instead of brittle. If frozen soil is regarded as a particle-reinforced composite material, then the debonding damage of ice particles and rate-dependent damage of soil matrix are taken into account. Based on this, a dynamic constitutive model of frozen soil under a multiaxial state is proposed. The theoretical results of the model agree well with the experimental results, verifying the rationality and applicability of the model.